Spicy food intake and overweight/obesity in rural Southwest China: findings from a cross-sectional study - Xiong, Huali; Zhao, Peng; Ma, Fengxun; Tang, Dayi; Liu, Daiqiang (Frontiers in Nutrition, 2025)
BackgroundSpicy food is an essential part of the culinary culture in rural southwest China, while little is known about the association between spicy food intake and overweight/obesity. This study was undertaken to explore the association between spicy food intake and overweight/obesity by a cross-sectional study.MethodWe enrolled 2,995 individuals aged 30–79 years living in Rongchang, Chongqing municipality, southwest China from The China Multi-Ethnic Cohort Study, which was deemed to be the largest cohort study in southwest China. A multivariable-adjusted logistic regression model was applied to estimate the association between spicy food intake and overweight/obesity. Additionally, subgroup and sensitivity analyses were performed to verify the stability of the results.ResultsA total of 81.67% of participants had the habit of consuming spicy food. The overall prevalence of overweight/obesity was 57.53%. Spicy food intake (OR = 2.913, 95%CI: 1.319–6.434) and frequency of spicy food intake (OR = 1.300, 95%CI: 1.164–1.452) were positively associated with overweight/obesity. Compared with the participants who never consumed spicy food, after adjusting for confounding factors, the adjusted ORs (95% CIs) in frequency of spicy food intake in 1–2 days/week, 3–5 days/week, 6–7 days/week subgroups were 3.985 (1.855–8.560), 4.381 (2.011–9.543), 6.515 (3.101–13.686), respectively. Subgroup analyses stratified by gender and age group, as well as sensitivity analyses, have consistently revealed a similar association between spicy food intake/the frequency of spicy food intake and overweight/obesity.ConclusionThis study could provide additional evidence for overweight and the obesity epidemic among rural adults in southwest China. Reducing spicy food intake might benefit from weight management.